My daughters and I - Theodore, Ifeoma JNR, E. (Epps Books service, 2013)
My Daughters and I is a collection of essays that engages the girl- child, mothers, and stakeholders in the fight for reproductive health alike #. In six short, informative and insightful essays, ifeoma theodore jnr, E. speaks to us and our children, about their concerns, their fears, their health. beautifully illustrated and packaged, this book should be a bedside staple for everyone.
Keywords: Non-Fiction